Educational and skill mismatches: differential effects on job satisfaction. A study applied to the Spanish job market - Sánchez Sánchez, Nuria; Fernández Puente, Adolfo C. (Estudios de Economía, 2015)
This paper focuses on the effect of educational and skill mismatches of workers on overall job satisfaction, and on certain job domains such as salary, number of working hours, promotion opportunities and type of activity performed. An ordered probit model is estimated by using a data set from the Survey of Quality of Working Life (ECVT). In addition to the variables related to these mismatches, other variables related to the characteristics of both the individual and the type of work are included. The results show that overeducated individuals show higher levels of dissatisfaction than those in which the fit is adequate. However, it also shows how individuals with a lower level of education than what would be required for the post do not reflect significant dissatisfaction levels. It is also evidence observed that individuals with less than the required skills are more dissatisfied than those with a proper matching. The results support the need to study both educational and skill mismatches separately.